The Rabbi Saved by Hitler's Jewish Soldiers : Rebbe Joseph Isaac Schneersohn and His Astonishing Rescue - Rigg, Bryan Mark, 1971- (Book collections on Project MUSE., 2016)
"A book that incorporates new research and analysis on the improbable tale of how Americans and Nazis collaborated to save Rabbi Joseph Isaac Schneersoh (1880-1950), the charismatic world-wide leader of a small ultra-Orthodox community of Hasidic Jews originating in western Russia and headquartered in Warsaw at the outbreak of Hitler's invasion of Poland"--